2012
DOI: 10.1074/jbc.m111.286211
|View full text |Cite
|
Sign up to set email alerts
|

Functional Architecture of the Outer Arm Dynein Conformational Switch

Abstract: Background: Ciliary dyneins monitor and respond to the mechanical state or curvature of the microtubular axoneme. Results: NMR chemical shift mapping and binding assays define functional subdomains within a key component (LC1) of this system. Conclusion: LC1 provides a direct tether between a dynein motor unit and the microtubule that modulates motor function. Significance: This study provides insight into the mechanism by which dyneins are coordinated during ciliary beating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
(38 reference statements)
3
19
1
Order By: Relevance
“…The labeling of His-tagged LC1 with Ni-NTA-nanogold at either the N- or the C-terminus ( Figure 3C ) suggested that LC1 is located on the γ MTBD region with its N-terminus oriented toward the tip and its C-terminus toward the base ( Figure 7B ). Previous mutational analysis showed that several basic residues in the N-terminal region are important for LC1's binding to the DMT ( King and Patel-King, 2012 ). Based on the LC1's orientation in our model, the N-terminal region should locate close to a microtubule ( Figure 7B ), and this model is consistent with the results of a previous mutation study.…”
Section: Discussionmentioning
confidence: 99%
“…The labeling of His-tagged LC1 with Ni-NTA-nanogold at either the N- or the C-terminus ( Figure 3C ) suggested that LC1 is located on the γ MTBD region with its N-terminus oriented toward the tip and its C-terminus toward the base ( Figure 7B ). Previous mutational analysis showed that several basic residues in the N-terminal region are important for LC1's binding to the DMT ( King and Patel-King, 2012 ). Based on the LC1's orientation in our model, the N-terminal region should locate close to a microtubule ( Figure 7B ), and this model is consistent with the results of a previous mutation study.…”
Section: Discussionmentioning
confidence: 99%
“…The surprisingly strong immunogenicity of the small amount of saliva proteins injected by both infected and non-infected blood-feeding arthropods offers another innovative but not widely used application, i.e. the correlation of humoral responses to saliva proteins with the frequency of insect bites [35,38]. This allows for the rapid and very straightforward determination of the success of vectorcontrol and -eradication strategies.…”
Section: Discussionmentioning
confidence: 99%
“…ticks) counter the host's immune response to saliva components by frequently switching expression between gene loci encoding variants of the same saliva proteins thus exposing the host to a changing pattern of saliva proteins; (iv) a factor of great concern is the variability of saliva components between arthropods in the field and their laboratory counterparts. Because of factors that are not completely understood yet (such as genetic drift in saliva proteins due to selective pressures, the presence of diverse populations of commensal bacteria, or co-infections in bloodfeeding arthropods), caution must be exercised when applying conclusions obtained from studying vector saliva proteins in laboratory arthropod strains to the conditions in the field; and (v) the levels of at least some saliva proteins fluctuates in a circadian manner [35].…”
Section: Arthropod-saliva and Pathogens: Unholy Alliance Or Unrealizementioning
confidence: 99%
“…Thus, although the activity of these two motors is apparently coordinated, they may function out of phase with each other; attachment of only a single outer arm dynein motor unit to the outer doublet B‐tubule was also observed previously by Ueno et al (). Not only do these two HCs have different inherent motor properties (Sale & Fox, ; Moss et al, ; Moss et al, ), the α HC but not the β HC is thought to associate with a highly conserved leucine‐rich repeat light chain (termed LC2 in sea urchin, DNAL1 in mammals and LC1 in Chlamydomonas ) that, at least in the equivalent Chlamydomonas γ HC, is located at the tip of the microtubule‐binding stalk, interacts with tubulin and might alter or modify mechanochemical coupling (Wu et al, ; Patel‐King & King, ; King & Patel‐King, ; Ichikawa et al, ).…”
Section: Dynein Power Stroke States Vary During Active Beatingmentioning
confidence: 99%